Keywords in Writing Studies - Heilker, Paul, 1962-; Vandenberg, Peter (Book collections on Project MUSE., 2014)
Keywords in Writing Studies is an exploration of the principal ideas and ideals of an emerging academic field as they are constituted by its specialized vocabulary. A sequel to the 1996 work Keywords in Composition Studies, this new volume traces the evolution of the field's lexicon, taking into account the wide variety of theoretical, educational, professional, and institutional developments that have redefined it over the past two decades.Contributors address the development, transformation, and interconnections among thirty-six of the most critical terms that make up writing studies. Looki.